Gerakan Reformasi 1998 dan Keterlibatan Mahasiswa di Tingkat Lokal: Kasus Sumatera Barat - Naldi, Hendra; Lionar, Uun; Yefterson, Ridho Bayu; Syafrina, Yelda (Universitas Hamzanwadi, 2022)
The 1998 Reformation Movement, which was led by students, was a social movement that had an impact on social and political changes in Indonesia in the following period. In the midst of the dryness of the study and writing of the history of the 1998 Reformation Movement, this paper will look at how the dynamics of students at the local level welcomed this movement through the eyes of local history. This study aims to describe the roots of the 1998 Reform Movement in Indonesia and then highlight the dynamics of students at the local level in West Sumatra in the 1998 Reform Movement. This study uses a historical research method consisting of four stages of activity in the form of heuristics, source criticism, interpretation, and historiography. The results showed that West Sumatran students were highly sensitive to the socio-political problems that engulfed the Indonesian nation at that time. As intellectuals, students respond to this issue by holding meetings, free pulpits, and holding demonstrations to criticize the government's policies and attitudes which are considered slow in solving the nation's problems. To facilitate coordination and consolidation of the movement, students formed the West Sumatera Student Communication Forum (FKMSB), which later became an important forum in gathering the strength of the students movement in West Sumatra during the transition period.Gerakan Reformasi 1998 yang dimotori oleh kalangan mahasiswa merupakan sebuah gerakan sosial yang berdampak terhadap perubahan sosial dan politik Indonesia pada periode berikutnya. Di tengah keringnya kajian dan penulisan sejarah Gerakan Reformasi 1998, maka tulisan ini akan melihat bagaimana dinamika mahasiswa di tingkat lokal menyambut gerakan ini melalui kacamata sejarah lokal. Penelitian ini bertujuan untuk menguraikan akar Gerakan Reformasi 1998 di Indonesia, dan kemudian menyoroti dinamika mahasiswa pada tingkat lokal di Sumatera Barat dalam Gerakan Reformasi 1998 tersebut. Penelitian ini menggunakan metode penelitian sejarah yang terdiri dari empat tahapan kegiatan berupa heuristik, kritik sumber, interpretasi, dan historiografi. Hasil penelitian menunjukkan bahwa mahasiswa Sumatera Barat memiliki sensitivitas yang tinggi atas permasalah sosial politik yang sedang melanda bangsa Indonesia ketika itu. Sebagai kalangan intelektual mahasiswa merespon isu tersebut dengan mengadakan pertemuan, mimbar bebas, hingga melakukan demonstrasi dalam rangka mengkritis kebijakan dan sikap pemerintah yang dinilai lamban dalam menyelesaikan persoalan bangsa. Untuk memudahkan koordinasi dan konsolidasi gerakan, mahasiswa membentuk Forum Komunikasi Mahasiswa Sumatera Barat (FKMSB) yang kemudian menjadi wadah penting dalam menghimpun kekuatan gerakan Mahasiswa di Sumatera Barat selama masa transisi tersebut.